Pengaruh Sistem Multi DIPA terhadap Anggaran Belanja Operasional Satuan Kerja Kementerian Agama - Sukadana, I Nengah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2022)
The Ministry of Religion Affairs has 3,000 Work Unit Offices managing 5,666 Dipa DIPA (budget implementation check list), it is known that the budget allocation for office operations and maintenance (002) of the Ministry of Religion is quite large. The Multi DIPA system currently used in Regional Office Work Units and Regency/City Offices makes the budget allocation for work unit operational fees (521115) large, reaching 12.1% of the operational expenditure ceiling (002). This study aims to determine the effect of the Multi DIPA System on the amount of the work unit operating fee budget at the Provincial and Regency / City Ministry of Religion Offices. With the method of implementing the One DIPA system scheme at the Ministry of Religion at the Regional and Regency/City levels, it can be seen that the current Multi DIPA system makes the operational expenditure budget of work units inefficient not in accordance with the principle of performance-based budgeting which emphasizes the concept of Value for money based on three main elements. , namely economy, efficiency, and effectiveness..